The Oxford handbook of music therapy - Edwards, Jane (Oxford Oxford University Press, 2016)
"Music therapy is growing internationally to be one of the leading evidence-based psychosocial allied health professions, meeting needs right across the lifespan. In the Oxford Handbook of Music Therapy, international leaders in the field from 10 countries have contributed their expertise to showcase contemporary music therapy. They share knowledgeable perspectives from multiple models of music therapy that have developed throughout the world, including Nordoff-Robbins Music Therapy."--Publisher description.
Keywords: Music -- Psychological aspects; Music therapy